Объяснение:
формула:а³+b³=(a+b)(a²-ab+b²)
a³-b³=(a-b)(a²+ab+b²)
1) р³+k³=(p+k)(p²-pk+k²)
2) a³-64=a³-4³=(a-4)(a²+4a+4²)=
=(a-4)(a²+4a+16)
3) 0,001m³-1=(0,1m)³-1³=
=(0,1m-1)((0,1m)²+0,1m+1)=
=(0,1m-1)(0,01m²+0,1m+1)
4) 8x³+27p³=(2x)³+(3p)³=
=(2x+3p)((2x)²-2x•3p+(3p)²)=
=(2x+3p)(4x²-6xp+9p²)
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Verified answer
Объяснение:
формула:а³+b³=(a+b)(a²-ab+b²)
a³-b³=(a-b)(a²+ab+b²)
1) р³+k³=(p+k)(p²-pk+k²)
2) a³-64=a³-4³=(a-4)(a²+4a+4²)=
=(a-4)(a²+4a+16)
3) 0,001m³-1=(0,1m)³-1³=
=(0,1m-1)((0,1m)²+0,1m+1)=
=(0,1m-1)(0,01m²+0,1m+1)
4) 8x³+27p³=(2x)³+(3p)³=
=(2x+3p)((2x)²-2x•3p+(3p)²)=
=(2x+3p)(4x²-6xp+9p²)